Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Moderasi Kebijakan Dividen: Studi Pada Perusahaan Properti, Real Estate dan Konstruksi Bangunan Yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017 - Ali Imron; Desi Kurniawati (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2020)
This study purposed to determine the effect of profitability proxy with Earning Per Share (EPS) and firm size is proxied by logarithm natural of total assets to firm value which proxied by Price Book Value (PBV) and to find out whether dividend policy proxied by Dividend Payout Ratio (DPR) be moderateted the relationship of profitability and firm size against firm value. The population in this study were all the property, real estate and building construction companies sector listed on Indonesia Stock Exchange for 2013 -2017. The sample in this study were 9 companies out of 62 population obtained through purposive sampling method. Data analysis techniques used in this study was Moderated Regression Analysis (MRA). The results of this study is: (1) Profitability has positive and significant impact to firm value. (2) Firm size has positive impact but not significant to firm value. (3) Dividend policy are able to moderate the effect of profitability against firm value. (4) Dividend policy can not moderate the effect of firm size against firm value.